Pengaruh Marketing Public Relations Terhadap Citra Merek: Studi Pada Restoran Joe’s Grill Swiss-Belhotel - Jeanica Christria; Diana Anggraeni (CoverAge: Journal of Strategic Communication, 2016)
Restaurant business in Indonesia is now more promising. Hanging out in restaurants has now become a teen and executive lifestyle. This increasingly tight competition makes restaurant manajer to market their restaurants, trying to instill a good brand image to consumers through public relations marketing activities needs to be done. This study aims to determine the effect of public relations marketing activities on brand image at the restaurant Joe's Grill Swiss-Belhotel Mangga Besar. Type of this research is explanative quantitative. The samples used were 61 consumers selected at random on the day of sampling. Methods Data collection using survei with questionnaires as instrument. The results of this study indicate that the variables of marketing public relations activities have a significant influence on brand image (R = 0.776) of Joe's Grill Restaurant Swiss-Belhotel Mangga Besar. The correlation level of the two variables is very strong that is 88.1%.